Reversible twisting-induced crystalline-polycrystalline transformation in cyanoacrylate crystals - Parthasarathy, Thiyagaraj; Bhowmik, Aritra; Bhattacharya, Biswajit; Mishra, Manish Kumar; Ghosh, Soumyajit (Chemical Communications, 2026)
We report cyanoacrylate-based organic crystalline materials that exhibit reversible hand-induced helical twisting through the combined action of 1D elasticity and 2D plasticity. These crystals twist and untwist without lattice damage, retaining their elastic integrity through pi slip-stacking and Cl & ctdot;Cl, C-H & ctdot;Cl, and Me & ctdot;Me interactions. Their unique integration of elastic recovery, plastic bending, and reversible twisting highlights their potential as mechanically adaptive materials for flexible and responsive devices.